Emerging trends and research foci of neuromyelitis optica spectrum disorder: a 20-year bibliometric analysis - Su, Yue; Ruan, Zhe; Li, Shicao; Li, Zhuyi; Chang, Ting (Frontiers in Immunology, 2023)
Background Neuromyelitis optica spectrum disorder (NMOSD) is a demyelinating syndrome of the central nervous system. A tremendous amount of literature on NMOSD has been published. This study aimed to perform a bibliometric analysis of the publications on NMOSD and show its hotspots and development trends. Methods We used the Web of Science Core Collection as a database and searched the literature published between 2002 and 2022. CiteSpace, VOSviewer, online bibliometric platform, and R-bibliometrix were used to conduct bibliometric analysis and network visualization, including the number of publications, citations, countries/regions, institutions, journals, authors, references, and keywords. Results A total of 3,057 publications on NMOSD were published in 198 journals by 200 authors at 200 institutions from 93 countries/regions. The United States published the most literature and made great contributions to this field. The Mayo Clinic was the institution with the largest number of publications. The journal with the most publications was Multiple Sclerosis and Related Disorders, and the most co-cited journal was Neurology. The author with the most publications was Fujihara, K., while the most frequently co-cited author was Wingerchuk, DM. The current research hotspots may be focused on “efficacy,” “multicenter,” “interleukin-6 receptor blockade,” “safety,” “azathioprine,” “tolerance,” and “adult”. Conclusion This study was the first bibliometric analysis of publications on the NMOSD field, visualizing its bibliometric characteristics and gaining insight into the direction, hotspots, and development of global NMOSD research, which may provide helpful information for researchers. Future research hotspots might be conducting randomized controlled trials on targeted immunotherapy in the NMOSD field.